PREPARASI CONTOH UJI PROFISIENSI UNTUK IDENTIFIKASI SENYAWA KIMIA BERBAHAYA - Evita Boes (Jurnal Kimia Terapan Indonesia, 2015)
The sample of proficiency test for hazard chemical compounds in organic and water sample has been made to identify hazard chemical compounds. Here, various matrix was added to these hazard chemical compound. The organic sample derived from organic waste added with dichloromethane as the solvent, undecane 100 µl/mL, 1,2-dimethylbenzene 12 µl/mL, diesel  100 µl/mL and tributhyl phosphate 10,02 µg/mL, whereas water sample derived from  water waste added with magnesium sulfate heptahydrate 120 µg/mL, sodium carbonate anhydrous 106 µg/mL, sodium sulfate anhydrous 284 µg/mL, calsium chloride  dyhidrate 222 µg/mL, dikhloromethane 2,5 µl/mL, polyethylene glycol 505,4 µg/mL, 3,5 dihydroxytoluene 10,05 µg/mL and α methyl-α-propyl succinimide 10,01 µg/mL. Hazard chemical compounds  that being added are Bis (3-methylbutyl) ethylphosphonate 10,04±0,31 µg/mL, Bis (2-chloroethyl) methylamine  20,59±0,14 µg/mL for organic sample and Pinacolyl methylphosphonate 9,80±0,18 µg/mL and Triethanolamine 14,84±0,10 µg/mL for water sample.  Homogeneity and stability are determined quantitatively using  GC-FPD (P-mode) and GC-FID with calibration curve using internal standard dibuty butylphosphonate, 2,6-dimethylphenol, dibutylphosphate and Bis (2-hydroxypropyl) aminoethanol with Relative Standard Deviation (RSD)  8,10 % and 12,40 µg/mL for Bis (3-methylbutyl) ethylphosphonate and 3,46 % and 14,19 µg/mL for Bis (2-chloroethyl) methylamine and 2,22 % and 11,28 µg/mL for Pinacolyl methylphosphonate and 2,70 % and 11,47 µg/mL for Triethanolamine.  Relative Standard Deviation is a homogeneity value with requirements below 20 % and stability is a degradation result which value is less than 30 %.Keywords: hazard chemical compounds, proficiency test, homogeneity, stability, relative standard deviation